SINTESIS DAN KARAKTERISASI NANOPARTIKEL MAGNETIT (FE3O4) DARI PASIR BESI SUNGAI BATANGHARI, JAMBI YANG DI ENKAPSULASI DENGAN SILIKA - Sinurat, Menita; Gusti, Diah Riski; Deswardani, Frastica; Safitri, Safitri; Sudibyo, Sudibyo (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This research aimed to produce magnetites from the residue of iron sand extract solution in HCl and the effect of silica encapsulation on the magnetite used XRD, SEM and FTIR characterization tools. The crystal size tended to increase in the magnetite encapsulated by silica (K (6%), L (9%), N (24%) and O (36%), because the perfect condensation and hydrolysis of the encapsulation material, while the M sample (12%) decreased the crystal size of 17.41 nm because the hydrolysis and condensation of the sample did not occur completely. The crystals in magnetite before and after being encapsulated with silica did not change. The transmittance of the typical functional groups of magnetite (Fe-O) and the typical functional groups of silica (Si-O-Si) tends to decrease after encapsulation with silica which caused the infrared absorbance of the molecules to increase high so that the presence of magnetite and silica is higher in the silica encapsulated sample The effect of variations in silica concentration on SEM characterization results is reduced agglomeration, particles that coincide and stick to the sample as the silica concentration increased with the smallest particle size found in the M sample (12%), namely the range of 10-50 nm. The residue of the iron sand extract solution with HCl can form nanomagnetites with an average particle size range below 100 nm.